Lumbar spine implant design with finite element method and determination of biomechanical effects - Taherzadeh, Paniz; Kelleci, Kubra; Ozer, Sevil (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2023)
Graphical/Tabular The restoration percentages of two different implants designed and simulated in six different directions are given in Figure A. Figure A. Restoration percentages of theimplant 1 and implant 2 devices in six different directionsPurpose: In this study, it was aimed to design a new pedicle-screw based posterior dynamic stabilization implant that can help stabilize the spine normally. In the study, two different implants were designed using the finite element method (FEM) and their biomechanical effects were compared.Theory and Methods: Stable and treated models of the lumbar spine with two different implants were simulated under physiological loading conditions according to Computed tomography data. Implant and device components were created with the SOLIDWORKS program. All designed devices were used together with ABAQUS CAD simulation program and MATLAB program to calculate range of motion, adjacent level effect and restoration percentages in six different directions (right-left axial rotation, right-left lateral bending and flexion-extension). In the study, 70% restoration percentage, which is an acceptable value in the movement of the spine with the implant, was tried to be achieved in all directions.Results: With the second device, which obtained optimum data and was found to be more flexible, a higher percentage of restoration was obtained in the Z and Y axes. Restoration values are 33% for extension, 53% for flexion, and 68% and 55% for lateral bending and axial rotations, respectively.Conclusion: It can be said that pedicle-screw implants designed with this simulation study will be applicable after experimental validation and clinical trials
Keywords: Posterior dynamic stabilization; Lumbar spine; Range of motion; Restoration; FEM; Engineering